Long‐term cognitive trajectories and heterogeneity in patients with schizophrenia and their unaffected siblings. (21st September 2018) - Islam, Md. A.; Habtewold, T. D.; van Es, F. D.; Quee, P. J.; van den Heuvel, E. R.; Alizadeh, B. Z.; Bruggeman, R.
Abstract : Objective: This study aimed to assess the heterogeneity and stability of cognition in patients with a non‐affective psychotic disorder and their unaffected siblings. In addition, we aimed to predict the cognitive subtypes of siblings by their probands. Method: Assessments were conducted at baseline, 3 and 6 years in 1119 patients, 1059 siblings and 586 controls from the Genetic Risk and Outcome of Psychosis (GROUP) study. Group‐based trajectory modeling was applied to identify trajectories and clustered multinomial logistic regression analysis was used for prediction modeling. A composite score of eight neurocognitive tests was used to measure cognitive performance. Results: Five stable cognitive trajectories ranging from severely altered to high cognitive performance were identified in patients. Likewise, four stable trajectories ranging from moderately altered to high performance were found in siblings. Siblings had a higher risk of cognitive alteration when patients' alteration was mild (OR = 2.21), moderate (OR = 5.70), and severe (OR = 10.07) compared with patients with intact cognitive function. The familial correlation coefficient between pairs of index patients and their siblings was 0.27 ( P = 0.003). Conclusions: The cognitive profiles identified in the current study might be suitable as endophenotypes and could be used in future genetic studies and predicting functional and clinical outcomes.